PKM Pengelolaan Bisnis Berbasis Entrepreneurship pada Pengrajin Keset Kaki Desa Panggungduwet - Sri Nathasya Br Sitepu (University of Merdeka Malang, 2020)
Entrepreneurship-based business management for doormats craftsmen in Panggungduwet Village. The number of craftsmen who participated in the PKM program was 10 people. PKM collaborates with the Panggungduwet Village government and the Faculty of Management, Ciputra University. Craftsmen problems: (1) Doormats business without innovation; (2) The conventional sales system; (3) The doormat business generates low income (less than 1 million/month); (4) Doormats craftsmen without entrepreneurship-based business management knowledge; (5) Doormats craftsmen are afraid to sell products through an online sales system; (6) The character of the craftsmen did not believe in himself. PKM goals: improve the quality of human resources from craftsmen, business management and reduce the number of poor people in Panggungduwet Village. The PKM activity methods consist of: Business Model Canvas analysis, business management innovation, and business evaluation. PKM Results: (1) Innovation of the entrepreneurship-based doormat business management system by developing customer relationships; (2) Marketing media innovation with social media; (3) Creating jobs for 20 people in Panggungduwet Village who become doormats craftsmen; (4) Increasing 15% income craftsmen; (5) Increase the understanding of craftsmen on the concept of entrepreneurship; (6) Increased self-confidence of craftsmen in running business operations and executing product sales with an online system.DOI: https://doi.org/10.26905/abdimas.v5i3.4201